PROCALCITONIN-EARLY BIOCHEMICAL MARKER FOR DIAGNOSIS, PROGNOSIS AND TREATMENT OF SEPSIS IN NEONATES AND ONCOLOGICAL PATIENTS WITH FEBRILE NEUTROPENIA - Nonkulovski, Danilo; Tankoska, Maja; Hristova, Mica Kimovska; Mandzukovska, Hristina Bicevska; Voinovska, Tamara; Martinova, Kata (Journal of Morphological Sciences; Vol 3 No 2 (2020): JMS, 2020)
Pediatric sepsis is a life-threatening condition, in which the immune system, instead of controlling the infection,causes damage to tissues and organs. The aim of this study was to determine the role of procalcitonin (PCT)in the early diagnosis of sepsis in high-risk infants and Oncological patients with febrile neutropenia,its prognostic value,and the role of PCT in the choice of antibiotic. The study is designed as retrospective-prospective, it is being worked at the PHI UC for Children Diseases Skopje. It includes 60 critical newborns and 40 Oncology patients.The examined group were divided into two subgroups:30 critical infants with bacterial sepsis in the intensive care unit and 20 Oncological patients with sepsis and febrile neutropenia.PCT  was determined the first 24h,3-5 days and 6-14 days of hospitalization.The value of PCT during the first 24 hours of admission was increased in all 50 patients.Most of them had signs of severe sepsis and few od them had signs of septic shock. In all of them,double parenteral antibiotic therapy was started.Seven patients has died in the first five days.After 3-5 days of the start of antibiotic therapy, PCT values ​​decreased.After the third measurement, PCT values ​​continued to decrease and in majority of the patients the antibiotic therapy was discontinued. By measuring the values ​of PCT, an early diagnosis of sepsis can be made. This is important to start with antibiotics to prevent sepsis and septic shock.The dynamic in the values ​​of PCT determine the duration of antibiotic,its modification,the rational uses of antibiotics and the emergence of resistance to it. Keywords : sepsis, procalcitonin (PCT), antibiotic therapy